ERYTHEMA MULTIFORME ASSOCIATED WITH MYCOBACTERIUM TUBERCULOSIS INFECTION - André Laureano; Cândida Fernandes; Jorge Cardoso (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Erythema multiforme is an uncommon, immune-mediated disorder that presents with cutaneous or mucosal lesions or both, that occurs as a hypersensitivity reaction in response to infections or drugs. Erythema multiforme is mostly associated with herpes simplex virus. The association with Mycobaterium tuberculosis infection was less frequently described. We present a case of an Erythema multiforme caused by Mycobacterium tuberculosis infection in a 35-year-old patient who was successfully treated with isoniazid, rifampicin, pirazinamid and ethambutol.